2022
DOI: 10.1073/pnas.2210036119
|View full text |Cite
|
Sign up to set email alerts
|

Potential for perceived failure of stratospheric aerosol injection deployment

Abstract: As anthropogenic activities warm the Earth, the fundamental solution of reducing greenhouse gas emissions remains elusive. Given this mitigation gap, global warming may lead to intolerable climate changes as adaptive capacity is exceeded. Thus, there is emerging interest in solar radiation modification, which is the process of deliberately increasing Earth’s albedo to cool the planet. Stratospheric aerosol injection (SAI)—the theoretical deployment of particles in the stratosphere to enhance reflection of inco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…Richter Jadwiga et al, 2018), but has seen little exploration with respect to climate impacts. Policymakers and planning practitioners often assess climate information on time horizons of 10 years or fewer (e.g., Bolson et al, 2013;DePolt, 2021;Pearman & Cravens, 2022;Keys et al, 2022). Thus, we portray our results consistently with how information could hypothetically be used for decisions about SAI deployment, governance, and evaluation.…”
Section: Analysis Metricssupporting
confidence: 68%
“…Richter Jadwiga et al, 2018), but has seen little exploration with respect to climate impacts. Policymakers and planning practitioners often assess climate information on time horizons of 10 years or fewer (e.g., Bolson et al, 2013;DePolt, 2021;Pearman & Cravens, 2022;Keys et al, 2022). Thus, we portray our results consistently with how information could hypothetically be used for decisions about SAI deployment, governance, and evaluation.…”
Section: Analysis Metricssupporting
confidence: 68%
“…Deser et al (2012,2020), for instance, have used large ensembles of simulations with climate models to show that natural variability can dominate regional changes in seasonal-mean temperature and precipitation over the coming decades. Similarly, Keys et al (2022) show that the signal of SAI forcing can be strongly masked by natural variability over large regions of the globe. The presence of natural climate variability has thus been a challenge for studies attempting to detect regional climate changes due to external forcing.…”
Section: Discussionmentioning
confidence: 86%
“…This result is not surprising given the challenges in disentangling the influences of anthropogenic aerosols, greenhouse gases, and internal variability on the forced response of regional precipitation (Lin et al, 2016;Deser et al, 2020;Ha et al, 2020). As shown in Keys et al (2022), internal variability can modulate or altogether mask the influences of SCI in the ARISE-SAI-1.5 simulation. Nonetheless, we cannot rule out higher prediction skill with more available training data.…”
Section: Discussionmentioning
confidence: 87%
“…This includes warming in parts of the extratropical Northern Hemisphere. Rather than suggesting that this is a robust, forced response to SCI, it is more likely that this is simply a reflection of internal variability, which is discussed in more detail in Keys et al (2022) and is also demonstrated by the large spread of ensemble member trends in figure s14. Furthermore, there is large variability in precipitation trends in the first decade since SCI initiation (figure s13(a)), but weaker trends in the longer 2045 to 2069 period (figure s13(d)).…”
Section: Time-evolving Climate Signals From Saimentioning
confidence: 95%
See 1 more Smart Citation